La campaña presidencial del herrerismo en 1946 desde El Debate - Carolina Cerrano (Nuevo mundo - Mundos Nuevos, 2017)
In this article we study the presidential campaign of herrerism in 1946, seen from El Debate. Luis Alberto de Herrera’s candidacy, the party’s advertising, the differentiation of his political proposal with that of his adversaries, specially with batllism, and the influence of peronism’s electoral success impact in Uruguay constitute the main themes of analysis. Herrerism built its media campaign through the worship of its leader’s persona, symbolized the electoral scenery as salvation or chaos, a “spiritual battle” between the present/past or the future. His political rethoric aspired to come out from the party’s narrow limits to conquer the nation beyond ideological differences, through a speech of order and safeguard of religion, freedom and authentic democracy. In his view, Uruguay’s fate was risking moral decay should we continue under batllism’s rule. A message of hope appeared on the horizon through peronism’s triumph, used as a symbol of the times of renovation in the continent.